1987
DOI: 10.1007/bf00199838
|View full text |Cite
|
Sign up to set email alerts
|

Influence of low-dose beta-interferon on natural killer cell activity in breast cancer patients subjected to chemotherapy

Abstract: The present study was designed to test whether immunomodulating doses of human beta-interferon would affect the natural cell-mediated cytotoxic function in untreated breast cancer patients or in those subjected to antitumor therapy. Analyses were performed on 11 breast cancer patients, 3 at stage 1 and 8 at stage 2, the latter being subjected to cyclophosphamide, methotrexate, 5-Fluorouracil (CMF) adjuvant chemotherapy. Five patients treated with CMF and 3 patients not subjected to adjuvant chemotherapy, recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…On this basis a study was designed to test whether the administration of LDIF, would affect NKA, an in vitro function possibly related to NR in vivo [6,7,11,12,16,19,20,27], in untreated breast cancer patients or in those subjected to chemotherapy according to the CMF (i.e., CTX + MTX + 5-FU) protocol. The results, reported previously [34], showed that (a) LDIF increased NKA of patients not subjected to chemotherapy; and (b) in patients treated with CMF, LDIF antagonized the depressive activity of CMF on N K function and significantly augmented NKA in those cases in which low basal activity was found at the time of LDIF administration. Parallel in vitro studies were carried out on peripheral MNC collected from cancer patients to be treated with LDIF or LDIF + CMF, to evaluate the boosting effects of [~IFN in vitro and to test whether a relationship could be found between in vivo and in vitro responses to this agent.…”
Section: Introductionmentioning
confidence: 52%
“…On this basis a study was designed to test whether the administration of LDIF, would affect NKA, an in vitro function possibly related to NR in vivo [6,7,11,12,16,19,20,27], in untreated breast cancer patients or in those subjected to chemotherapy according to the CMF (i.e., CTX + MTX + 5-FU) protocol. The results, reported previously [34], showed that (a) LDIF increased NKA of patients not subjected to chemotherapy; and (b) in patients treated with CMF, LDIF antagonized the depressive activity of CMF on N K function and significantly augmented NKA in those cases in which low basal activity was found at the time of LDIF administration. Parallel in vitro studies were carried out on peripheral MNC collected from cancer patients to be treated with LDIF or LDIF + CMF, to evaluate the boosting effects of [~IFN in vitro and to test whether a relationship could be found between in vivo and in vitro responses to this agent.…”
Section: Introductionmentioning
confidence: 52%